RELATIONSHIP OF WEAR-FRICTION PROPERTIES AND ENERGY-LOAD OF FRICTION COUPLES OF BRAKE DEVICES - Kindrachuk, Myroslav; Zhuravlyev, Dmytro; Prikolotin, Sergiy; Andreychikov, Yevgen; Burava, Oleksandr (Problems of Friction and Wear, 2023)
The relationship between wear and friction properties and the energy load of friction pairs of braking devices during external friction of different friction pairs of a belt-pad brake is considered. The decisive influence on the dynamic coefficient of friction (f) and the intensity of wear (In) of the maximum surface temperature ( ) on discrete contacts of friction pairs is shown. Graphical dependences of the form f=f(pa, )and In =I(pa, ), λ = λ( ), а = а( ) and НВ = НВ( ) were analyzed (pa – impulse specific loads; λ and а – coefficients heat and temperature, HB – Brinell hardness) and establish their interdependence with the temperatures of the friction surfaces. In a correctly designed metal friction element of any type of braking device, the values of the ratio of the areas of matte and polished (working) surfaces must be maintained. At the same time, the increase in the area of the matte surface is achieved by the introduction of external constructive elements. In drum and belt-pad brakes, this is the implementation of ribs, deflectors, grooves, protrusions, etc.), in disc-pad brakes, internal developed surfaces are used in self-ventilated disks (protrusions, half ribs, ribs, channels, etc.). This approach is connected with the need to intensify the forced cooling of metal friction elements, which are heat energy accumulators in any type of braking device. Therefore, the second and third subsystems of various types of braking devices are considered from the point of view of the interaction of metal friction elements with high-speed flows of the washing medium, which reduce their energy load. When evaluating the intensity of cooling simultaneously with forced cooling in a belt and drum-pad brake, it is necessary to take into account the conductive type of heat exchange in the couplings "pulley rim – fastening protrusion and "drum rim - side wall". The presence of a fastening protrusion significantly affects the intensity of circulation of the main and additional heat flows in the rim of the pulley. The side wall of the drum plays a significant role in forming the thermo-stabilization state of its rim. A comparative analysis of changes in the main operating parameters was made and their interdependence was established on a model belt-pad brake during the operation of friction pairs in pulse and three-shaft braking modes.